SOCIAL INTERPRETATION OF â€œWAJAH OTTâ€ IN POLITICAL COMMUNICATION MANAGEMENT CONTEXT OF PAUL RICOUER ANALYSIS (HAND CATCH OPERATION KPK -â€œOTTâ€™S FACEâ€) - Sumartias, Suwandi; Amina, Nurtyasih Wibawanti Ratna (Economic and Bussiness Faculty, Dr Soetomo University, 2018)
The writing purpose to understand and criticize Social Text